Fostering career readiness among final year students: lived experiences of counselors in public institutions of higher education - Syed Mahmood, Syarifah Rohaniah; Ssekamanya, Siraje Abdallah; Mansor, Norwati; Ahmad, Noorlila (Secholian Publication, 2026)
The transition from higher education to the workforce presents significant challenges for graduating students, particularly in aligning academic preparation with industry expectations. In Malaysia, counsellors in Public Institutions of Higher Education (PIHE) play a crucial role in equipping students with the skills, knowledge, and confidence needed for career readiness. Despite this important function, limited research has explored the lived experiences and effective strategies employed by these counsellors in facilitating students' career development. This study addresses this gap by examining the practices of counsellors within selected Malaysian PIHEs, aiming to shed light on their contributions in enhancing graduate employability. This study employs a phenomenological approach to explore the lived experiences of counsellors in Malaysian PIHEs, focusing on the strategies they use to foster career readiness among graduating students. In-depth interviews were conducted with six counsellors from Public Institutions of Higher Education (PIHE) located in Kuala Lumpur, Selangor, and Perak, Malaysia. The data collected was analyzed using thematic analysis, which identified five strategies used by the counsellors: organizing programs and workshops, designing career modules, collaborating with industry, conducting group counselling sessions, and providing individual coaching. The findings will furnish empirical evidence to help graduate programs, educators, and novice counselors in assisting graduating students with the transition into the workforce